Pengaruh Komunikasi Word OF Mouth Terhadap Keputusan Pembelian Konsumen Pizza Hut di Kota Padang - Tika Meliya Sari (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
Abstract This study aims to describe purchasing decisions and word of mouth communication and the influence between the two variables. This type of research is quantitative with causal associative methods. The population in this study were all consumers who had made a purchase at the Pizza Hut of Padang City where the amount was unknown. The sample in this study amounted to 96 people. The sampling technique used purposive sampling, where the researcher focused the sample of consumers who bought Pizza Hut in Padang City. Collecting data using a questionnaire based on the Likert Scale that tested its validity and reliability. F count is 35,111 with sig. 0,000 <0,05, the word of mouth communication variable has a significant influence on purchasing decisions.. Keywords: Purchasing Decision, Word of Mouth Communication